Contenção farmacológica de jacaré-tinga Caiman crocodilus Linnaeus, 1758 com cetamina S (+) e cetamina racêmica, isolada ou em associação com o midazolam - Hirano, Líria Queiroz Luz (2011)
CHAPTER 2: This work was developed with the purpose of evaluating and comparing two different dosages of ketamine and midazolam in Caiman crocodilus. We used twelve common caiman divided into two groups of six animals. Group 1 received midazolam 2 mg/kg IM and ketamine 20 mg/kg IM, as in group 2, we used the same dosage of midazolam with ketamine at 40 mg/kg IM. We assessed the physiological parameters of body temperature, heart and respiratory rates, also the righting reflex, muscle relaxation, head support, corneal reflex and response to nocciceptive stimulation. The beginning of sedative action, interval of the optimum effect and recovery time of the animals did not differ (p>0,05) between the two protocols, being 7.5 ± 4.18 minutes, 257.5 ± 39.6 minutes and 450 ± 122.47 minutes for the group 1 and 5.83 ± 2.04 minutes, 279.17 ± 80.4 minutes and 550 ± 104.89 minutes in group 2, respectively. There were no changes in physiological parameters and all the animals showed satisfactory muscle relaxation, however, the protocols did not promote non-response to nocciceptive stimuli. We concluded that the concomitant use of midazolam 2 mg/kg associated with ketamine 20 mg/kg is more compensatory than the protocol composed of these drugs with the dissociative agent at a dose of 40 mg/kg. CHAPTER 3: The aim of this study was to compare the sedative effects of racemic ketamine and S (+) ketamine in Caiman crocodilus. We used twelve common caiman divided into two groups of six animals. Group 1 received racemic ketamine at a dose of 20 mg/kg IM, as in group 2, we used S (+) ketamine (20 mg/kg IM). We assessed physiological parameters, righting reflex, muscle relaxation, head support, corneal reflex and response to nocciceptive stimulation. All crocodilians presented lethargic behavior with a decrease in aggression and attempted to escape muscle relaxation and difficulty in sustaining head. The optimum effect of sedative action and duration of maximum effect did not differ (p>0,05) between the two protocols, being 6.66 ± 0.96 minutes and 81.66 ± 39.2 minutes for group 1 and 10. 83 ± 3.76 minutes and 68.33 ± 30.98 minutes for group 2, respectively. The recovery in group 1 occurred at 110 ± 48.99 minutes and in group 2, at 115 ± 55.04 minutes, values statistically equal (p>0,05). The physiological parameters of body temperature, respiratory and heart rates were not statistically different (p>0,05) between baseline (t0) and other times analyzed. It was concluded that there is no relevant differences in relation to periods anesthetics and adverse effects between the use of ketamine in the racemic form and S (+) pure, at a dose of 20 mg/kg IM in Caiman crocodilus. Furthermore, the protocols evaluated are indicated for using in pharmacological restraint of common caiman for non-invasive procedures.